METODE DOA SEBAGAI PENGOBATAN PSIKOTERAPI - Syamsidar, (AL-IRSYAD AL-NAFS: JURNAL BIMBINGAN DAN PENYULUHAN ISLAM, 2022)
Human life is never apart from problems that require solutions to solve them. These problems are both related to physical and psychological conditions. Solving problems experienced by humans can sometimes be treated through medical or medical treatment and can also be psychological. This is because along with the development of the times, human needs are increasingly complex and diverse. Many new things then emerge to meet the demands of human needs which keep turning and coming and going.